Microencapsulation of Purple-Fleshed Sweet Potato Anthocyanins with Chitosan-Sodium Tripolyphosphate by Using Emulsification-Crosslinking Technique - Umi Laila; Rochmadi Rochmadi; Sri Pudjiraharti (Institute for Research and Community Services (LPPM) ITB, 2019)
Anthocyanins extracted from purple-fleshed sweet potato were encapsulated using emulsification-crosslinking technique with chitosan acted as polymer and sodium tripolyphosphate as cross-linker. The parameters influencing microencapsulation were investigated i.e. stirring intensity and polymer concentration, pH of polymer and crosslinker solution, and also ratio of anthocyanins extract (core) to polymer concentration by characterizing the properties of obtained microcapsules. Stirring intensity of 1600 rpm achieved microcapsules with smaller mean diameter, narrower particle size distribution, and greater encapsulation efficiency than that of 1200 rpm for each similar polymer concentration. The research revealed that pH of 3.0 gave the greatest encapsulation efficiency and antioxidant activity of microcapsules. However, the different of mean diameter and particle size distribution of microcapsules for all of pH solution variation was not significant. Ratio of anthocyanins extract to polymer concentration 75% (w/w) possessed the greatest encapsulation efficiency, the biggest mean diameter and the widest particle size distribution between all of ratio variation. Meanwhile, ratio of 150% was selected for further analysis (microstructure and FT-IR) because it gave narrower particle size distribution and smaller mean diameter with its encapsulation efficiency was only little different from others ratio. Microstructure analysis by SEM revealed sphere and irregular microparticles. FT-IR analysis revealed that that there was bonding and interaction among anthocyanin, chitosan, and tripolyphosphate ion.